2008
DOI: 10.1073/pnas.0800482105
|View full text |Cite
|
Sign up to set email alerts
|

A new influenza virus virulence determinant: The NS1 protein four C-terminal residues modulate pathogenicity

Abstract: The virulence of influenza virus is a multigenic trait. One determinant of virulence is the multifunctional NS1 protein that functions in several ways to defeat the cellular innate immune response. Recent large-scale genome sequence analysis of avian influenza virus isolates indicated that four C-terminal residues of the NS1 protein is a PDZ ligand domain of the X-S/T-X-V type and it was speculated that it may represent a virulence determinant. To test this hypothesis, by using mice as a model system, the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
310
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(323 citation statements)
references
References 42 publications
9
310
0
4
Order By: Relevance
“…This result implies that the attenuation could be caused by the NS1 ED of H17N10. Compared to the sequence of PR8 NS1 ED, there is a C-terminal 11-aa truncation in H17N10 NS1 ED, which constitutes a nucleolus localization signal, a binding domain of the cellular premRNA processing protein PABII and a PDZ domain binding motif related to virus replication and pathogenicity (Chen et al, 1999;Jackson et al, 2008). Whether the C-terminal 11-aa truncation of H17N10 ED affects the replication of NS1-H17N10/NEP-PR8 virus should be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This result implies that the attenuation could be caused by the NS1 ED of H17N10. Compared to the sequence of PR8 NS1 ED, there is a C-terminal 11-aa truncation in H17N10 NS1 ED, which constitutes a nucleolus localization signal, a binding domain of the cellular premRNA processing protein PABII and a PDZ domain binding motif related to virus replication and pathogenicity (Chen et al, 1999;Jackson et al, 2008). Whether the C-terminal 11-aa truncation of H17N10 ED affects the replication of NS1-H17N10/NEP-PR8 virus should be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, all three human H7N9 viruses have acquired the 627K mutation in their PB2 protein, which may have significantly contributed to their pathogenicity and lethality in humans. The NS1 protein of the novel H7N9 viruses is truncated by a stop codon at position 218, which creates a deletion of the PDZ-binding domain, a protein-protein interaction domain that has been implicated in the pathogenicity of the 1918 virus and highly pathogenic H5N1 viruses [15]. The PB1-F2 protein has been shown to be related to the increased pathogenicity of the 1918 virus and highly pathogenic H5N1 viruses [16,17].…”
Section: Molecular Signatures Of the Novel H7n9 Virusesmentioning
confidence: 99%
“…Although influenza virus pathogenicity is a multigenic trait, it has been shown that the NS1 protein is an important virulence determinant in avian, swine and human influenza viruses (Seo et al, 2002;Li et al, 2006;Jackson et al, 2008). Studies have also shown that plant viral RSS proteins are important virulence/pathogenicity factors (Cronin et al, 1995;Ding et al, 1995).…”
Section: Introductionmentioning
confidence: 99%